Vibration mitigation in offshore wind turbines via tuned mass damper. (15th March 2019) - Ghassempour, Mina; Failla, Giuseppe; Arena, Felice
Highlights: Omnidirectional tuned mass damper used for vibration control in 5 MW offshore wind turbine. Fully-coupled, aero-hydro-servo-elastic simulations implemented in dedicated software. Best tuning frequency changes with operational wind speed due to nonlinear rotor dynamics. Best tuning frequency equal to first support-structure modal frequency only in parked rotor state. Fixed mass and wind-speed dependent adjustable stiffness are suggested for best TMD design. Abstract: This paper deals with vibration mitigation via tuned mass damper in bottom-fixed, horizontal-axis offshore wind turbines. Focusing on a baseline 5-MW turbine mounted on a monopile, equipped with an omnidirectional tuned mass damper inside the nacelle, the study explores a wide range of potential tuning frequencies, mass and damping ratios, in both operational and parked rotor conditions. It is found that the tuning frequency to attain optimal reduction of structural vibrations shall be changed depending on the wind velocity in operational conditions while, in contrast, is generally equal to the natural frequency of the first support structure modes only in parked conditions. This result, attributable to inherent non-linearity of rotor dynamics, demonstrates that a conventional design of the tuned mass damper based on the natural frequencies of the support structure modes may not be suitable for offshore wind turbines.